Philippines : Report on the Observance of Standards and Codes Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2004)
This report summarizes the reviews of compliance and consistency with key principles and standards applicable to financial sector of the Philippines. It reviews compliance with the Basel Core Principles for Effective Banking Supervision, the Committee on Payment and Settlement Systems Core Principles for Systemically Important Payment Systems, the International Organization of Securities Commissions Objectives and Principles of Securities Regulations, the International Association of Insurance Supervisors Supervisory Principles, and the Code of Good Practices in Transparency in Monetary and Financial Policies.